Human Behaviour and Behaviourism: A Psychological perdpective on Robert J. Conley’s Cherokee Dragon - Kumari, R Janatha; Jenifer, S Sushma; Nair, Sheeba S (International Journal of Psychosocial Rehabilitation, 2020)
The behaviour of a person is not a hereditary activity but it can be learnt and also influenced by the environment and circumstances that take hold of human emotions. American psychologist and father of behaviourism, John Broadus Watson popularized the scientific theory of behaviourism. He emphasised in the external behaviour of people and their reactions on the given situations, rather than the internal mental state of the person. Behaviours and reactions are the only objective method to get an insight into human actions. Robert J. Conley is a Cherokee (Native Indian Tribe in America) writer and historian has brought out the life and behaviour of Dragging Canoe (Tsiya Gansini) in the tenth novel of ‘Real People Series,’ Cherokee Dragon Cherokee tribe is the descendants of a large and powerful ‘American Indian Tribe’. Dragging Canoe was not recognised as a patriotic leader because he rose to prominence only during, ‘the American Revolution’. This paper aims to bring out the elements of behaviourism through Watson’s theory in the character Dragging Canoe.